MicroRNA-449c-5p alleviates lipopolysaccharide-induced HUVECs injury via inhibiting the activation NF-κb signaling pathway by TAK1. (June 2022) - Fu, Qinghui; Yu, Wenqiao; Fu, Shuiqiao; Xu, Zhipeng; Zhang, Shaoyang
Abstract: Background: Acute kidney injury caused by sepsis has become a hotspot of scientific research in recent years. Since the kidney is the most abundant of all organs with vascular endothelium, activation and injury of vascular endothelial cells is a main reason to renal dysfunction. In our research, we identify that miRNA-449c-5p can alleviate HUVECs injury through inhibiting the NF-κb signaling pathway activation by targeting TAK1 with the method of bioinformatics and in vitro experiment. Methods: Datasets of GSE28750 and GSE94717 were obtained from the GEO database. Differential analysis was performed on the two data sets using the GEO2R tool of the GEO database, and the miRNA-mRNA network was further constructed. Lipopolysaccharide (LPS) against Human umbilical vein endothelial cells induced an in vitro model of AKI were used for verification. RT-PCR, Western blotting, ELISA, CCK8, EDU and luciferase reporter genes were used to verify whether miR-449c-5p could alleviate the apoptosis of vascular endothelial cells and the release of inflammatory factors during the progression of sepsis by inhibiting the expression of TAK1. Results: TAK1 was identified as a direct target of miR-449c-5p by luciferase reporter gene assay, and TAK1 expression was negatively regulated by miR-449c-5p. Overexpression of miR-449c-5p promoted cell viability, inhibited apoptosis rate and inhibited the expression of inflammatory cytokines in HUVECs after LPS stimulation. Moreover, miR-449c-5p deactivated NF-κB signaling by targeting TAK1. Conclusion: In cell model experiments, it was found that miRNA-449c-5p could inhibit the release of LPS induced inflammatory cytokine, inhibit the occurrence of apoptosis and promote cell proliferation by inhibiting the expression of TAK1. Therefore, thus miRNA-449c-5p played a protective role on vascular endothelial cells. Highlights: At present, there are few reports about miR-449c-5p. Only two studies have reported miR-449c-5p before. In this study, miR-449c-5p was found for the first time to have a possible inhibitory effect on inflammatory response. miR-449c-5p may have a protective mechanism to vascular endothelial cells.